Current understanding of KATP channels in neonatal diseases: focus on insulin secretion disorders - Quan Yi; Barszczyk Andrew; Feng Zhong-ping; Sun Hong-shuo (Acta Pharmacologica Sinica, 2016)
ATP-sensitive potassium (KATP) channels are cell metabolic sensors that couple cell metabolic status to electric activity, thus regulating many cellular functions. In pancreatic beta cells, KATP channels modulate insulin secretion in response to fluctuations in plasma glucose level, and play an important role in glucose homeostasis. Recent studies show that gain-of-function and loss-of-function mutations in KATP channel subunits cause neonatal diabetes mellitus and congenital hyperinsulinism respectively. These findings lead to significant changes in the diagnosis and treatment for neonatal insulin secretion disorders. This review describes the physiological and pathophysiological functions of KATP channels in glucose homeostasis, their specific roles in neonatal diabetes mellitus and congenital hyperinsulinism, as well as future perspectives of KATP channels in neonatal diseases.